The Implementation of Education Policy - Sri Mariya; Nurhizrah Gistituati; Rusdinal Rusdinal (International Journal of Educational Dynamics, 2022)
Education policy has been formulated with an educational vision and mission to build a society for lifelong learning by fostering cultural values and Pancasila. The importance of cooperation in realizing the policy by designing a clear policy and rules. Ar-Risalah is one of the Islamic universities in the city of Padang which will be used as a study in policy implementation. This type of research is descriptive research through interviews and literature study. Based on the results of the research, the implementation of the policy is stated in the school's vision and mission and is carried out in an order that is jointly prepared for students. Meanwhile, policies for teachers are regulated through a contract system while being a teacher at school. Policy implementation is carried out differently at each school level, both elementary, junior high, and high school which is in line with the vision and mission of the Ar-Risalah educational college.